Identification and functional characterization of the MYB transcription factor GmMYBLJ in soybean leaf senescence - Bao, Guohua; Xu, Xiao; Yang, Jing; Liu, Juanjuan; Shi, Tianran; Zhao, Xiaoxuan; Li, Xuyan; Bian, Shaomin (Frontiers in Plant Science, 2025)
Leaf senescence is an important agronomic trait that significantly influences the quality and yield of soybeans. v-Myb avian myeloblastosis viral oncogene homolog (MYB) transcription factors are considered crucial regulators governing leaf senescence, which can be utilized to improve agronomic traits in crops. However, our knowledge regarding the functional roles of soybean MYBs in leaf senescence is extremely limited. In this study, GmMYBLJ, a CCA1-like MYB, was identified and functionally characterized with respect to leaf senescence. The GmMYBLJ protein is localized in the nucleus, and a high accumulation of its transcripts was observed in nodules and embryos. Notably, GmMYBLJ was highly expressed in soybean senescent leaves and was transcriptionally induced by dark or NaCl treatment, as confirmed by histochemical GUS staining analysis. Ectopic overexpression of GmMYBLJ in Arabidopsis not only led to earlier leaf senescence, reduced chlorophyll content, and increased MDA accumulation but also promoted the expression of several WRKY family transcription factors and senescence-associated genes, such as SAG12 and ORE1. Further investigation showed that overexpression of GmMYBLJ accelerated Arabidopsis leaf senescence under darkness and in response to Pst DC3000 infection. Moreover, transgenic soybean plants overexpressing GmMYBLJ grew faster and exhibited accelerated senescence under salt stress. DAB staining analysis showed that GmMYBLJ induced ROS accumulation in soybean hairy roots and Arabidopsis leaves. Collectively, our results provided useful information into the functional roles of GmMYBLJ in both age-dependent and stress-induced senescence.